Understanding Attachment to Place in the context of the 2021 Tajogaite eruption crisis and recovery, La Palma - Rosie Rice; Clive Oppenheimer (Volcanica)
Previous research on place attachment in disaster contexts has focused on its influence on risk perception, evacuation, relo- cation, and its re-establishment post-disaster. However, consideration of place attachment in risk management has hitherto been little studied. The 2021 eruption of Volcán de Tajogaite, La Palma, significantly damaged urban areas and some residents still wait to be rehoused or allowed to return to their homes. Here we show that: (i) place attachment, particularly to the home, was largely neglected during the emergency yet strongly influenced resident experiences, and (ii) attachment to place is being re-established amongst the communities in temporary housing, encouraging people to stay on the island. Drawing on these findings, we make recommendations for ‘place-based’ emergency management with broad relevance to volcanic islands.